2022
DOI: 10.3389/froh.2022.863231
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gene Expression Patterns for Oral Epithelial Cell Functions in Periodontitis

Abstract: The structure and function of epithelial cells are critical for the construction and maintenance of intact epithelial surfaces throughout the body. Beyond the mechanical barrier functions, epithelial cells have been identified as active participants in providing warning signals to the host immune and inflammatory cells and in communicating various detailed information on the noxious challenge to help drive specificity in the characteristics of the host response related to health or pathologic inflammation. Rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Consequently, they are essential for coordinating gene expression and directing various biological responses, and their dysregulation is strongly associated with human diseases [69]. Despite the significance of TFs in disease, periodontal research has focused primarily on identifying differentially expressed genes and deducing their functions through associated signaling pathways [16][17][18][19][20][21][22][23][24][25][70][71][72][73][74]. Moreover, changes in TFs expression are not always accompanied by alterations in functional activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they are essential for coordinating gene expression and directing various biological responses, and their dysregulation is strongly associated with human diseases [69]. Despite the significance of TFs in disease, periodontal research has focused primarily on identifying differentially expressed genes and deducing their functions through associated signaling pathways [16][17][18][19][20][21][22][23][24][25][70][71][72][73][74]. Moreover, changes in TFs expression are not always accompanied by alterations in functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Different omics technologies have benefited personalized medicine by enabling simultaneous and in-depth whole genome molecular analysis in response to environmental cues at any given time [14,15]. In particular, in the numerous in vitro and in vivo studies that have contributed to a partial understanding of the molecular mechanisms underlying the pathogenesis of periodontitis, the most frequently utilized technique has been the transcriptome microarray [16][17][18][19][20][21][22][23][24][25]. In this study, we employed high-throughput RNA sequencing (RNA-Seq), the standard approach for understanding the changes in RNA levels underlying cellular responses induced by environmental perturbations [26].…”
Section: Introductionmentioning
confidence: 99%
“…Further, when comparing the group that underwent preventive Metformin administration versus the group on water prior to disease induction, our results showed that in the Metformin group, the epithelial cells upregulated Krt76 and Krt6a (genes important for epithelial immune reaction and differentiation [ 50 ]), Gas5 (a gene important for glucocorticoid receptor control which modulates insulin resistance [ 51 ]), and Fxyd3 (a regulator of Na + /K + ATPases, maintaining osmotic equilibrium and membrane potential in epithelial cells [ 52 ]) (Additional file 12 : Fig. S5B, Additional file 16 : Table S1, Additional file 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a particular study, it was found that CALD1 expression was significantly increased in the brains of people with AD compared to those without the condition and that CALD1 may be involved in the production of amyloid beta, a protein that is believed to be a key contributor to the development of AD [ 17 , 18 ]. Some research has suggested that CALD1 may be involved in the development of periodontitis, a type of gum disease characterised by inflammation and loss of the tissue and bone that support the teeth [ 19 , 20 ]. It was found that CALD1 expression was significantly increased in the gingiva of people with periodontitis compared to those without the condition and that CALD1 may be involved in the immune response to periodontitis.…”
Section: Discussionmentioning
confidence: 99%